Numerical Analysis Of Fluid Flow Characteristics In Coal–Woodchips Combustion Within A Circulating Fluidized Bed Furnace (Case Study: Up Sebalang) - Moh. Rosifaul Azis; Harmen Harmen; Amrul Amrul (Eduvest - Journal of Universal Studies, 2025)
The increase in energy demand in the industrial era 4.0 has encouraged the transition to renewable energy, but Indonesia's dependence on coal is still high. One of the promising decarbonization strategies is high co-firing technology, which is the mixing of biomass (such as woodchips) with coal in coal-fired power plant boilers. Previous studies have generally focused on the emission and combustion efficiency aspects without delving deeply into the fluid flow characteristics in the furnace. Therefore, this study aims to numerically analyze the characteristics of fluid flow in the combustion process of coal and woodchips mixture in the Circulating Fluidized Bed (CFB) boiler of PLTU UP Sebalang. The methods used are Computational Fluid Dynamics (CFD) simulation with Eulerian multiphase model, k-ε turbulence model, and discrete phase for coal particle injection. Simulations were carried out for three fuel variations: 100% coal, 90% coal + 10% woodchips, and 80% coal + 20% woodchips. The results showed that an increase in the proportion of woodchips lowered the average temperature in the furnace from 945°C to 810°C and caused the heat distribution to be uneven. The pressure distribution also decreases as the woodchips fraction increases, with the negative pressure at the cyclone outlet increasing from -310 Pa to -401 Pa. Validation of the simulation results against the field data showed an average deviation of between 2–9%, still within the tolerance limit, although affected by the imperfections of the measuring tool and the limitations of the model on the effects of induced fan drafts.